Seismic behaviour of vernacular architecture - Varum, H. (2015)
Vernacular buildings are in several seismic prone regions a relevant part of the building stock. They represent an important part of the of the cultural legacy, and of the technological and heritage context of the society. The present paper presents a revision of the effect of recent earthquake disasters in old buildings, and discusses the influence of the main structural elements in the vulnerability of these buildings, as well as the more common failure mechanisms. Finally, it is presented a review on the elements that more contribute to the seismic behaviour and performance of vernacular buildings.